Allogeneic hematopoietic cell transplantation for myelofibrosis aged 70 years or older: a study from the German Registry for Stem Cell Transplantation - Gagelmann, Nico; Schuh, Claudia; Zeiser, Robert; Stelljes, Matthias; Bethge, Wolfgang Andreas; Wulf, Gerald; Teschner, Daniel; Klein, Stefan; Wagner-Drouet, Eva; Jost, Edgar; Dreger, Peter; Flossdorf, Sarah; et al. (Transplantation and cellular therapy, 2024)
Current consensus recommends hematopoietic cell transplantation (HCT) for patients with myelofibrosis with intermediate or high-risk disease and age of less than 70 years. However, a higher chronological age should not be prohibitive for the eligibility decision in general, acknowledging that current life expectancy for the general population aged 70 years is ∼15 years, and current numbers of patients transplanted at 70 years or older is steadily increasing. The following study aimed to evaluate characteristics and outcomes of HCT in 115 myelofibrosis patients aged 70 years or older. This is a retrospective multicenter study, using the German Registry for Stem Cell Transplantation and Cellular Therapy (DRST). Adult myelofibrosis patients were included who received HCT up until 2021. Patients with secondary leukemia were excluded. Main endpoints were HCT demographics over time and outcomes after HCT (including overall survival, relapse incidence, non-relapse mortality, and graft-versus-host disease/relapse-free survival). Numbers of HCT increased over the past decade, with a significant spike since 2019. Comorbidity status of transplanted patients improved over time, while reduced-intensity conditioning was the preferred HCT platform, especially in most recent years. The 3-year overall survival was 55% (95% confidence interval [CI], 44%-65%). The 1-year cumulative incidence of relapse was 7% (95% CI, 3%-13%) and the 1-year cumulative incidence of non-relapse mortality was 22% (95% CI, 14%-31%). The 3-year graft-versus-host disease and relapse-free survival was 37% (95% CI, 27%-47%). Driver mutation genotype (in particular, non-CALR/MPL genotype) appeared to be the only variable that was significantly and independently associated with better survival in multivariable analysis, whereas neither comorbidity index nor dose intensity of pre-transplant conditioning appeared to influence outcome. This study demonstrated feasibility of curative treatment with HCT for myelofibrosis aged 70 or older, with significant increases in HCT numbers and improved fitness of older adults over recent years.